American cutaneous leishmaniasis triggered by electrocoagulation - Martins, Sofia Sales (2018)
Cutaneous leishmaniasis is usually transmitted by infected phlebotomine sand fly bites that initiate local cutaneous lesions. Few reports in the literature describe other modes of transmission. We report a case of a previously healthy 59-year-old woman who underwent electrocoagulation to remove seborrheic keratosis confirmed by dermatoscopy. Three months later, a skin fragment tested positive for Leishmania culture; the parasite was identified as L. (V.) braziliensis. Trauma may generate inflammatory cascades that favor Leishmania growth and lesion formation in previously infected patients. American cutaneous leishmaniasis is a dynamic disease with unclear pathophysiology because of continually changing environments, demographics, and human behaviors.